The Progress of Gene Therapy for Leber's Optic Hereditary Neuropathy - Zhang, Yong; Tian, Zhen; Yuan, Jiajia; Liu, Chang; Liu, Hong l.; Ma, Si Qi; Li, Bin (Current Gene Therapy, 2017)
Introduction: Leber's Optic Hereditary Neuropathy (LHON) is a common cause of teenaged blindness in both eyes for which there is currently no effective treatment. In 1871, the German ophthalmologist Theodor Leber was the first to describe the clinical characteristics of his namesake disease, and through unremitting efforts over the past 100 years, researchers have continued to increase their understanding of LHON. In recent years, using gene therapy, several groups have obtained breakthroughs in the treatment of the disease. Conclusion: In this article, we will review the challenging journey that researchers faced towards our current understanding of LHON, and describe the transition of gene therapy research for LHON from the bench to bedside.
Keywords: Translational medicine